Highly waterproof grouting slurry for shield tunnel and preparation method thereof
By using modified fibers and polymer additives in the grouting slurry, a superimposed layered arrangement and three-dimensional connection network is formed, which solves the problem of water leakage and penetration of existing waterproof grouting slurry during construction, and achieves efficient waterproofing Performance and mechanical properties are suitable for shield tunnel construction in complex groundwater systems.
Patent Information
- Application Number
- CN202410796994.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The existing waterproof grouting slurry is prone to water leakage and penetration in projects with long construction cycles, resulting in deterioration of the construction environment and difficulties in subsequent construction, especially in complex groundwater systems.
Using a high waterproof grouting slurry, containing cement, stone sand, fly ash, sodium-based bentonite, modified fibers, polymer additives, curing agents, quick-setting agents and water reducing agents, through modified fibers and polymerization The combination of additives enhances the mechanical properties and waterproof properties of the slurry, forms a superimposed layered arrangement and three-dimensional connection network, and improves the migration resistance and penetration difficulty of water molecules.
The excellent stone rate and injectable performance of the slurry are achieved, the long-term waterproofing effect is maintained, the leakage and penetration of groundwater are avoided, and the good construction environment is maintained, which significantly improves the use value and market value.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of shield construction materials, and in particular to a highly waterproof grouting slurry for shield tunnels and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, rail transit construction has developed rapidly. Shield construction is an advanced construction method in underground rail transit construction projects. In shield construction, the use of grouting slurry is indispensable. During the shield excavation process, gaps will be formed between the segments and the surrounding soil. If they are not filled in time, the stratum will lose support, causing surface settlement and deformation above the tunnel. By injecting slurry behind the segments, these gaps can be quickly filled, providing necessary support, effectively controlling surface settlement, and protecting the safety of ground buildings, underground pipelines, and construction personnel. Therefore, the use of grouting slurry and its performance are crucial to the construction of shield tunnels.
[0003] With the gradual development of rail transit construction across the country, choosing reasonable grouting slurry according to different address conditions has become the preferred solution for shield construction operations. For example, in areas with complex groundwater systems, the performance of grouting slurry should focus on mechanical stability and waterproof performance to prevent loosening and collapse of the stratum. Highly waterproof grouting slurry can form an integrated waterproof barrier, effectively improve the waterproof performance of the joints of the pipe segments, prevent groundwater from pouring into the excavation surface, and avoid gushing during construction. However, the existing waterproof grouting slurry has poor long-term waterproofing effect. When used in projects with a long construction period, although gushing will not occur, it is still prone to leakage, infiltration and other phenomena, which deteriorates the construction environment and creates difficulties for subsequent construction.
[0004] Therefore, in order to effectively solve the above problems, the present application provides a high-waterproof grouting slurry for shield tunnels and a preparation method thereof. The high-waterproof grouting slurry prepared in the present application has excellent stone setting rate and injectability while maintaining excellent waterproof performance and mechanical properties, thereby meeting the use needs in areas with complex groundwater systems, avoiding leakage and infiltration of groundwater in tunnels, maintaining a good construction environment, maintaining good long-term waterproof effects, and having very excellent use value and market value. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a highly waterproof grouting slurry for shield tunnels. The raw materials include, by mass: 10 to 20 parts of cement, 60 to 80 parts of stone sand, 30 to 40 parts of fly ash, 10 to 15 parts of sodium bentonite, 15 to 25 parts of modified fiber, 4 to 10 parts of polymer additives, 2 to 8 parts of curing agent, 6 to 12 parts of accelerator, 0.1 to 2 parts of water reducer, and 60 to 100 parts of water.
[0006] As a preferred solution, the mass ratio of the cement material to the polymer additive is (1.2~2):(0.6~1).
[0007] As a preferred solution, the mass ratio of the cement material, sodium bentonite and modified fiber is (1.2~2): (1.2~1.5): (1.8~2).
[0008] As a preferred solution, the mass ratio of the cement material, sodium bentonite and modified fiber is (1.2~2):1.4:1.8.
[0009] As a preferred solution, the cement material is ordinary Portland cement or Portland cement.
[0010] As a preferred solution, the cement material is ordinary Portland cement P.O32.5.
[0011] As a preferred solution, the average particle size of the stone sand is 2.25~6.5mm.
[0012] As a preferred solution, the fineness of the fly ash is ≤25%.
[0013] As a preferred solution, the mass ratio of the cement material, stone sand and fly ash is (1.2~2): (7~7.5): (3~3.5).
[0014] As a preferred solution, the mass ratio of the cement, stone sand and fly ash is (1.2~2): (7.2~7.3): (3.4~3.5).
[0015] As a preferred scheme, the preparation method of the modified fiber includes the following steps: S1: evenly mix the carbon fiber and sericite powder and add them to deionized water, add dodecyl calcium sulfate, succinic anhydride and silane coupling agent at the same time, heat to 60-65°C, and ultrasonically disperse at 400-500W for 8-10h to obtain a pretreated product; S2: evenly disperse the pretreated product in a DMF solution, add trimesic acid and mix evenly, heat to 60-75°C, stir and dropwise add a DMF solution of copper acetate, the dropping time is 0.5-1h, and after the dropping is completed, keep warm and stir for 2-3h to obtain a product solution; S3: add ammonia water to the product solution to adjust the pH to 7-7.5, stir for 0.5-1h, centrifuge the product solution, filter and wash, and vacuum dry at 50-60°C to obtain the product.
[0016] As a preferred solution, the mass ratio of the carbon fiber, sericite powder, calcium dodecyl sulfate, succinic anhydride and silane coupling agent is (2-2.5): (0.5-1): (0.5-1.1); (1-1.5): (0.3-0.5).
[0017] As a preferred solution, the mass ratio of the carbon fiber, sericite powder, calcium dodecyl sulfate, succinic anhydride and silane coupling agent is (2.2-2.5): (0.6-0.8): (0.8-1); (1.4-1.5): (0.3-0.45).
[0018] As a preferred solution, the mass ratio of the pre-treated product, trimesic acid and cupric acetate is (1.5-2): (0.6-0.8): (1.2-1.8).
[0019] As a preferred solution, the average particle size of the sericite powder is 0.1-1 mm.
[0020] As a preferred solution, the average diameter of the carbon fibers is 4-8 μm; the average length of the carbon fibers is 1.5-2 mm.
[0021] In this application, the mechanical properties, waterproof properties and stone rate of the grouting slurry after use can be greatly increased by adding the above-mentioned modified fibers. The modified carbon fiber can play a good fixed connection role with the sericite powder by showing the role of active groups, and increase the affinity and dispersion effect of the composite fiber in gel materials such as cement, and can play a good dispersion role after the grouting slurry is solidified; when the carbon fiber and sericite powder are compounded, the lamellar morphology of the sericite powder can promote the paving effect of the carbon fiber in the slurry, so that after the slurry is solidified, a superimposed layered arrangement effect is formed inside, thereby greatly enhancing the migration resistance of the slurry to water molecules after solidification, and increasing the migration path; on the other hand, with the coordination generation of skeleton particles on the surface of carbon fiber and sericite powder, the structural support of the skeleton particles can provide the system with linear support and connection of points and lines when external forces act, thereby greatly enhancing the strength of the system, and the presence of the skeleton particles can assist in the adsorption of water molecules in the system after solidification, thereby enhancing the removal effect of internal water molecules and increasing the difficulty of water penetration.
[0022] As a preferred solution, the preparation method of the polymer additive comprises the following steps: S1: adding methyl methacrylate, isooctyl acrylate and isobornyl acrylate to an acryloyl chloride solution, introducing nitrogen and adding an initiator, heating to 60-80°C for reaction for 3-4 hours to generate a prepolymer; S2: mixing the obtained prepolymer with acrylamide and deionized water, stirring evenly, adding an initiator, and heating to 55-70°C under nitrogen protection until the reaction is complete; S3: adding acetone to the product obtained in S2 for cleaning, filtering and drying the product, and obtaining the product after completion.
[0023] As a preferred solution, the mass ratio of methyl methacrylate, isooctyl acrylate, isobornyl acrylate and acryloyl chloride is (4-5): (2-3): (0.2-0.5): (12-20).
[0024] As a preferred solution, the mass ratio of methyl methacrylate, isooctyl acrylate and isobornyl acrylate is 4.4:2.1:0.4:(14-18).
[0025] As a preferred solution, the mass ratio of acryloyl chloride to acrylamide is (12-20); (25-35).
[0026] As a preferred solution, the mass ratio of acryloyl chloride to acrylamide is (14-18); (25-30).
[0027] As a preferred solution, the initiator is potassium persulfate or ammonium persulfate.
[0028] The polymer additive added in this application can effectively improve the waterproof and mechanical properties of the grouting slurry after use. The long molecular chain formed by the polymer additive can form a good embedding effect inside the system through the action of the aqueous system, and provide good agglomeration resistance for the solidified grouting system through the adsorption of cement particles, thereby stabilizing the uniformity of the entire system and preventing the premature aggregation and exclusive solidification of cement particles. The gel system of cement can help form a certain three-dimensional connection network in the solidified system, thereby enhancing the interaction between active molecules and enhancing mechanical properties. The presence of long molecular chains can limit the movement frequency of water molecules in the system and reduce the content of infiltrated water molecules, thereby achieving excellent waterproof stability during long-term use.
[0029] As a preferred solution, the curing agent is at least one of calcium formate, aluminate, sulphoaluminate and phosphate.
[0030] As a preferred solution, the curing agent is calcium formate.
[0031] As a preferred solution, the accelerating agent is a combination of sodium silicate and potassium silicate.
[0032] As a preferred solution, the mass ratio of sodium silicate to potassium silicate is (2-3):(0.5-1).
[0033] As a preferred solution, the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.
[0034] As a preferred solution, the water reducer is a polycarboxylate water reducer.
[0035] The second aspect of the present application provides a method for preparing the above-mentioned high waterproof grouting slurry for shield tunnels, and the preparation method comprises the following steps: S1: adding modified fiber, polymer additive, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring in a mixer at 40~50℃ and 80~120rpm for 30~50min to obtain the obtained grouting slurry after mixing evenly.
[0036] The beneficial effects of this application are:
[0037] 1. The highly waterproof grouting slurry for shield tunnels provided in the present application has excellent stone setting rate and injectability while maintaining excellent waterproof and mechanical properties, thereby meeting the use needs in areas with complex groundwater systems, avoiding leakage and infiltration of groundwater in tunnels, maintaining a good construction environment, and maintaining good long-term waterproof effects, and has very excellent use value and market value.
[0038] 2. The highly waterproof grouting slurry for shield tunnels provided in the present application, wherein the added modified fiber can greatly increase the waterproof performance and stone formation rate of the grouting slurry after use; the modified carbon fiber can play a good fixing connection role with the sericite powder by expressing the role of active groups, and increase the affinity and dispersion effect of the composite fiber in gel materials such as cement, and can play a good dispersion role after the grouting slurry is solidified; when the carbon fiber and sericite powder are compounded, the lamellar morphology of the sericite powder can promote the paving effect of the carbon fiber in the slurry, thereby forming a superimposed layered arrangement effect inside the slurry after solidification, thereby greatly enhancing the migration resistance of the slurry to water molecules after solidification, and increasing the migration path.
[0039] 3. The highly waterproof grouting slurry for shield tunnels provided in the present application, the added modified fibers can greatly increase the mechanical properties of the grouting slurry after use; accompanied by the coordination generation of skeleton particles on the surface of carbon fiber and sericite powder, it can provide the system with point-line integrated linear support and connection through the structural support of the skeleton particles when external force acts, thereby greatly enhancing the strength of the system, and the presence of the skeleton particles can assist in the adsorption of water molecules in the system after solidification, thereby enhancing the removal effect of internal water molecules and increasing the difficulty of water penetration.
[0040] 4. The highly waterproof grouting slurry for shield tunnels provided in the present application, the added polymer additives can effectively improve the waterproof and mechanical properties of the grouting slurry after use; the long molecular chains formed by the polymer additives can form a good embedding effect inside the system through the action of the aqueous system, and provide good agglomeration resistance for the solidified grouting system through the adsorption of cement particles, thereby stabilizing the uniformity of the entire system and preventing the premature aggregation and exclusive solidification of cement particles. The gel system of cement can help form a certain three-dimensional connection network in the solidified system, thereby enhancing the interaction force between active molecules and enhancing the mechanical properties. The presence of long molecular chains can limit the movement frequency of water molecules in the system. DETAILED DESCRIPTION
[0041] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0042] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0043] Example 1
[0044] Example 1 The first aspect provides a highly waterproof grouting slurry for shield tunnels. The raw materials include, by mass: 14 parts of cement, 72 parts of stone sand, 35 parts of fly ash, 14 parts of sodium bentonite, 18 parts of modified fiber, 8 parts of polymer additives, 6 parts of curing agent, 8 parts of accelerator, 0.6 parts of water reducer, and 80 parts of water.
[0045] The cement material is ordinary Portland cement P.O32.5; the average particle size of the stone sand is 2.85mm; the fineness of the fly ash is ≤25%.
[0046] The sodium bentonite was purchased from the first-grade sodium bentonite product sold by Kunjian Mineral Products Processing Plant in Lingshou County.
[0047] The preparation method of the modified fiber includes the following steps, calculated by mass: S1: 2.4 parts of carbon fiber and 0.75 parts of sericite powder are mixed evenly and added to 100 parts of deionized water, and 0.86 parts of dodecyl calcium sulfate, 1.4 parts of succinic anhydride and 0.44 parts of 3-aminopropyltriethoxysilane are added at the same time, and the temperature is raised to 60°C, and ultrasonic dispersion is performed at 500W for 8.5 hours to obtain a pretreated product; S2: 1.6 parts of the pretreated product are evenly dispersed in 50 parts of DMF solution, and 0.65 parts of trimesic acid are added and mixed evenly, and the temperature is raised to 70°C and stirred and 1.5 parts of DMF solution of copper acetate (a total of 20 parts) are added dropwise, and the dropping time is 0.8 hours. After the dropping is completed, the product solution is kept warm and stirred for 2.5 hours to obtain a product solution; S3: Ammonia water is added to the product solution to adjust the pH to 7.2, and after stirring for 1 hour, the product solution is centrifuged, filtered and washed, and vacuum dried at 55°C to obtain the product.
[0048] The average particle size of sericite powder is 0.6 mm; the average diameter of carbon fiber is 6 μm, and the average length of carbon fiber is 1.6 mm. The carbon fiber is purchased from products of corresponding sizes sold by Shenzhen Turing New Materials Co., Ltd.
[0049] The preparation method of the polymer additive comprises the following steps, calculated by mass: S1: adding 4.4 parts of methyl methacrylate, 2.1 parts of isooctyl acrylate and 0.4 parts of isobornyl acrylate to 16 parts of acryloyl chloride solution, introducing nitrogen and adding 0.06 parts of potassium persulfate, heating to 68°C for reaction for 3 hours to generate a prepolymer; S2: mixing the obtained prepolymer with 26 parts of acrylamide and 180 parts of deionized water, stirring evenly, adding 0.12 parts of potassium persulfate, heating to 65°C under nitrogen protection until the reaction is complete; S3: adding acetone to the product obtained in S2 for washing, filtering and drying the product, and obtaining the product after completion.
[0050] The curing agent is calcium formate; the accelerating agent is a combination of sodium silicate and potassium silicate, with a mass ratio of 2.2: 1. The water reducing agent is an early strength polycarboxylic acid water reducing agent with a water reduction rate of 23.2%, which is an industrial-grade product purchased from Henan Mingzhixin Chemical Products Co., Ltd.
[0051] The second aspect of this embodiment provides a method for preparing the above-mentioned high waterproof grouting slurry for shield tunnels, and the preparation method comprises the following steps: S1: adding modified fiber, polymer additive, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring in a mixer at 45°C and 100 rpm for 45 minutes to mix evenly.
[0052] Example 2
[0053] Example 2 The first aspect provides a highly waterproof grouting slurry for shield tunnels. The raw materials include, by mass: 16 parts of cement, 70 parts of stone sand, 30 parts of fly ash, 121 parts of sodium bentonite, 20 parts of modified fiber, 6 parts of polymer additives, 6 parts of curing agent, 8 parts of accelerator, 0.6 parts of water reducer, and 80 parts of water.
[0054] The cement material is ordinary Portland cement P.O32.5; the average particle size of the stone sand is 2.85mm; the fineness of the fly ash is ≤25%.
[0055] The sodium bentonite was purchased from the first-grade sodium bentonite product sold by Kunjian Mineral Products Processing Plant in Lingshou County.
[0056] The preparation method of the modified fiber includes the following steps, calculated by mass: S1: 2.4 parts of carbon fiber and 0.75 parts of sericite powder are mixed evenly and added to 100 parts of deionized water, and 0.86 parts of dodecyl calcium sulfate, 1.4 parts of succinic anhydride and 0.44 parts of 3-aminopropyltriethoxysilane are added at the same time, and the temperature is raised to 60°C, and ultrasonic dispersion is performed at 500W for 8.5 hours to obtain a pretreated product; S2: 1.6 parts of the pretreated product are evenly dispersed in 50 parts of DMF solution, and 0.65 parts of trimesic acid are added and mixed evenly, and the temperature is raised to 70°C and stirred and 1.5 parts of DMF solution of copper acetate (a total of 20 parts) are added dropwise, and the dropping time is 0.8 hours. After the dropping is completed, the product solution is kept warm and stirred for 2.5 hours to obtain a product solution; S3: Ammonia water is added to the product solution to adjust the pH to 7.2, and after stirring for 1 hour, the product solution is centrifuged, filtered and washed, and vacuum dried at 55°C to obtain the product.
[0057] The average particle size of sericite powder is 0.6 mm; the average diameter of carbon fiber is 6 μm, and the average length of carbon fiber is 1.6 mm. The carbon fiber is purchased from products of corresponding sizes sold by Shenzhen Turing New Materials Co., Ltd.
[0058] The preparation method of the polymer additive comprises the following steps, calculated by mass: S1: adding 4.4 parts of methyl methacrylate, 2.1 parts of isooctyl acrylate and 0.4 parts of isobornyl acrylate to 16 parts of acryloyl chloride solution, introducing nitrogen and adding 0.06 parts of potassium persulfate, heating to 68°C for reaction for 3 hours to generate a prepolymer; S2: mixing the obtained prepolymer with 26 parts of acrylamide and 180 parts of deionized water, stirring evenly, adding 0.12 parts of potassium persulfate, heating to 65°C under nitrogen protection until the reaction is complete; S3: adding acetone to the product obtained in S2 for washing, filtering and drying the product, and obtaining the product after completion.
[0059] The curing agent is calcium formate; the accelerating agent is a combination of sodium silicate and potassium silicate, with a mass ratio of 2.2: 1. The water reducing agent is an early strength polycarboxylic acid water reducing agent with a water reduction rate of 23.2%, which is an industrial-grade product purchased from Henan Mingzhixin Chemical Products Co., Ltd.
[0060] The second aspect of this embodiment provides a method for preparing the above-mentioned high waterproof grouting slurry for shield tunnels, and the preparation method comprises the following steps: S1: adding modified fiber, polymer additive, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring in a mixer at 45°C and 100 rpm for 45 minutes to mix evenly.
[0061] Comparative Example 1
[0062] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber includes the following steps, calculated by mass: S1: 2.4 parts of carbon fiber and 0.75 parts of sericite powder are mixed evenly and added to 100 parts of deionized water, and 0.86 parts of dodecyl calcium sulfate are added at the same time, and ultrasonic dispersion is performed at 500W for 8.5 hours to obtain a pretreated product; S2: 1.6 parts of the pretreated product are evenly dispersed in 50 parts of DMF solution, and 0.65 parts of trimesic acid are added and mixed evenly, the temperature is raised to 70°C and stirred, and 1.5 parts of DMF solution of cupric acetate (20 parts in total) is added dropwise, the dropping time is 0.8 hours, and after the dropping is completed, the temperature is kept and stirred for 2.5 hours to obtain a product solution; S3: ammonia water is added to the product solution to adjust the pH to 7.2, and after stirring for 1 hour, the product solution is centrifuged, filtered and washed, and vacuum dried at 55°C to obtain the product.
[0063] Comparative Example 2
[0064] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber comprises the following steps, calculated by mass: S1: 2.4 parts of carbon fiber and 0.75 parts of sericite powder are uniformly mixed and added to 100 parts of deionized water, and 0.86 parts of dodecyl calcium sulfate, 1.4 parts of succinic anhydride and 0.44 parts of 3-aminopropyltriethoxysilane are added at the same time, and the temperature is raised to 60°C, and ultrasonically dispersed at 500W for 8.5h to obtain a pretreated product; S2 : Disperse 3.5 parts of the pretreated product evenly in 65 parts of DMF solution, add 0.26 parts of trimesic acid and mix evenly, heat to 70°C, stir and dropwise add 0.84 parts of DMF solution of cupric acetate (10 parts in total), the dropping time is 0.5h, after the dropping is completed, keep warm and stir for 2.5h to obtain the product solution; S3: add ammonia water to the product solution to adjust the pH to 7, and stir for 1h, then centrifuge the product solution, filter and wash, and vacuum dry at 55°C to obtain.
[0065] Comparative Example 3
[0066] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the sericite powder is 1.8 mm.
[0067] Comparative Example 4
[0068] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average diameter of the carbon fiber is 25 μm; the average length of the carbon fiber is 6 mm, and the corresponding size products are purchased from Shenzhen Turing New Materials Co., Ltd.
[0069] Comparative Example 5
[0070] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the polymer additive comprises the following steps, calculated by mass: S1: adding 8 parts of methyl methacrylate, 1.5 parts of isooctyl acrylate and 0.1 part of isobornyl acrylate to 24 parts of acryloyl chloride solution, introducing nitrogen and adding 0.06 parts of potassium persulfate, heating to 68°C to react for 3 hours to generate a prepolymer; S2: mixing the obtained prepolymer with 26 parts of acrylamide and 180 parts of deionized water, stirring evenly, adding 0.12 parts of potassium persulfate, and heating to 65°C under nitrogen protection until the reaction is complete; S3: washing the product obtained in S2 with acetone, filtering and drying the product, and obtaining the product after completion.
[0071] Comparative Example 6
[0072] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the polymer additive comprises the following steps, calculated by mass: S1: adding 4.4 parts of methyl methacrylate, 2.1 parts of isooctyl acrylate and 0.4 parts of isobornyl acrylate to 16 parts of acryloyl chloride solution, introducing nitrogen and adding 0.06 parts of potassium persulfate, heating to 68°C to react for 3 hours to generate a prepolymer; S2: mixing the obtained prepolymer with 48 parts of acrylamide and 240 parts of deionized water, stirring evenly, adding 0.16 parts of potassium persulfate, and heating to 65°C under nitrogen protection until the reaction is complete; S3: washing the product obtained in S2 with acetone, filtering and drying the product, and obtaining the product after completion.
[0073] Comparative Example 7
[0074] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the high waterproof grouting slurry for the shield tunnel, calculated by mass, includes the following raw materials: 14 parts of cement, 72 parts of stone sand, 35 parts of fly ash, 14 parts of sodium bentonite, 18 parts of modified fiber, 2.5 parts of polymer additive, 6 parts of curing agent, 8 parts of accelerator, 0.6 part of water reducer, and 80 parts of water.
[0075] Performance Evaluation
[0076] Consistency: The consistency of the grouting slurry prepared in the embodiment and the comparative example was tested 8 hours after grouting using a consistency meter. The test value was the average value of 10 tests and recorded in Table 1.
[0077] Anti-penetration pressure: The grouting slurries of the embodiments and comparative examples were tested for anti-penetration pressure with reference to standard GB / T 50082-2009. The results were expressed as the maximum no-water seepage pressure. The test values were averaged over 10 tests and recorded in Table 1.
[0078] Stone rate: The grouting slurry prepared in the embodiment and the comparative example was subjected to grouting curing, and the stone rate after curing was tested, stone rate % = stone body dry mass / original total mass × 100%, and the test value was the average value of 10 tests and recorded in Table 1.
[0079] Mechanical strength: The mechanical strength of the grouting slurry obtained in the embodiment and the comparative example after curing was tested with reference to the standard GB / T 50081-2019, and the test value was the average value of 10 tests and recorded in Table 1.
[0080] Table 1 Performance test results
[0081]
[0082] According to the examples and comparative examples and the data in Table 1, it can be seen that by adopting the special technical solution in the present application, Examples 1 and 2 can achieve excellent stone rate and mechanical properties while also having excellent waterproofness and operability, thereby avoiding the phenomenon of penetration and water leakage in the long-term use of shield construction, maintaining the construction environment and reducing the difficulty of subsequent construction. Comparative Examples 1 to 7 do not adopt the special technical solution, resulting in the grouting slurry prepared therefrom being significantly worse than Examples 1 and 2 in various performance tests after curing, which strongly proves that the technical effect of the technical solution adopted in the present application is a non-obvious technical effect.
Claims
1. A highly waterproof grouting slurry for shield tunnels, characterized in that: In parts by mass, the raw materials include: 10-20 parts of cement, 60-80 parts of stone sand, 30-40 parts of fly ash, 10-15 parts of sodium bentonite, 15-25 parts of modified fiber, 4-10 parts of polymer additive, 2-8 parts of curing agent, 6-12 parts of accelerator, 0.1-2 parts of water reducer, and 60-100 parts of water; The cement material is ordinary Portland cement or Portland cement; The average particle size of the stone sand is 2.25~6.5mm; The fineness of the fly ash is ≤25%; The mass ratio of the cement material and the polymer additive is (1.2-2): (0.6-1); The preparation method of the modified fiber comprises the following steps: S1: uniformly mixing carbon fiber and sericite powder and adding them into deionized water, adding dodecyl calcium sulfate, succinic anhydride and silane coupling agent at the same time, heating to 60-65°C, and ultrasonically dispersing at 400-500W for 8-10h to obtain a pretreated product; S2: uniformly dispersing the pretreated product in a DMF solution, adding trimesic acid and mixing uniformly, heating to 60-75°C, stirring and dripping a DMF solution of copper acetate, the dripping time is 0.5-1h, and after the dripping is completed, the temperature is kept and stirred for 2-3h to obtain a product solution; S3: adding ammonia water to the product solution to adjust the pH to 7-7.5, stirring for 0.5-1h, centrifuging the product solution, filtering and washing, and drying in a vacuum at 50-60°C to obtain the product; The mass ratio of the carbon fiber, sericite powder, calcium dodecyl sulfate, succinic anhydride and silane coupling agent is (2-2.5): (0.5-1): (0.5-1.1); (1-1.5): (0.3-0.5); The mass ratio of the pre-treated product, trimesic acid and copper acetate is (1.5-2): (0.6-0.8): (1.2-1.8); The average particle size of the sericite powder is 0.1-1 mm; The average diameter of the carbon fiber is 4-8 μm; the average length of the carbon fiber is 1.5-2 mm; The preparation method of the polymer additive comprises the following steps: S1: adding methyl methacrylate, isooctyl acrylate and isobornyl acrylate to an acryloyl chloride solution, introducing nitrogen and adding an initiator, heating to 60-80° C. for reaction for 3-4 hours to generate a prepolymer; S2: mixing the obtained prepolymer with acrylamide and deionized water, stirring evenly, adding an initiator, and heating to 55-70° C. under nitrogen protection until the reaction is complete; S3: adding acetone to the product obtained in S2 for washing, filtering and drying the product, and obtaining the product after completion; The mass ratio of methyl methacrylate, isooctyl acrylate, isobornyl acrylate and acryloyl chloride is (4-5): (2-3): (0.2-0.5): (12-20); The mass ratio of acryloyl chloride to acrylamide is (12-20): (25-35); The curing agent is at least one of calcium formate, aluminate, sulphoaluminate and phosphate.
2. The highly waterproof grouting slurry for shield tunnel according to claim 1, characterized in that: The mass ratio of the cement material, sodium bentonite and modified fiber is (1.2-2): (1.2-1.5): (1.8-2).
3. The high waterproof grouting slurry for shield tunnel according to claim 2, characterized in that: The mass ratio of the cement, stone sand and fly ash is (1.2-2): (7-7.5): (3-3.5).
4. The highly waterproof grouting slurry for shield tunnel according to claim 3 is characterized in that: The quick-setting agent is a composition of sodium silicate and potassium silicate; the mass ratio of the sodium silicate to the potassium silicate is (2-3): (0.5-1).
5. The method for preparing a highly waterproof grouting slurry for a shield tunnel according to claim 4, characterized in that: The water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.
6. A method for preparing a highly waterproof grouting slurry for a shield tunnel according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1: adding modified fiber, polymer additive, curing agent, accelerator and water reducing agent into water and mixing and dispersing them uniformly; S2: adding the remaining raw materials and stirring them in a mixer at 40-50°C and 80-120rpm for 30-50min to mix them uniformly.
